PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE TERHADAP KINERJA PERUSAHAAN: SEBUAH TINJAUAN LITERATUR - -, Nilawati; Arizah, Ainun (AKRUAL : Jurnal Akuntansi dan Keuangan, 2025)
This study aims to identify and analyze the relationship between ESG disclosure and corporate performance through a systematic literature review approach to 25 articles published in SINTA-accredited national journals between 2020 and 2025. The results of the study show that ESG disclosure generally contributes positively to corporate performance, both financially and non-financially, although there are variations in the results depending on the industrial sector and performance indicators used. Legitimacy theory, stakeholder theory, and signaling theory are used as theoretical bases in analyzing the relationship. This study provides academic and practical contributions in increasing understanding of the importance of ESG disclosure as part of corporate sustainability strategies in Indonesia.